The effect of digital technology usage on higher vocational student satisfaction: the mediating role of learning experience and learning engagement - Zhang, Xiangping; Qian, Wensheng; Chen, Chengxi (Frontiers in Education, 2024)
The fourth industrial revolution and the digital transformation represented by Industry 4.0 have stimulated digital innovations in economic and social spheres, accelerating the structural transformation of the labor market and increasing the demand for high-quality vocational education and training. The influence of digital technology on student satisfaction is acknowledged; nonetheless, the precise mechanisms via which it impacts student satisfaction related to learning experience and learning engagement remain largely unexplored. This study seeks to investigate the impact of digital technology usage on student satisfaction of Chinese higher vocational college students, mediated by learning experience and learning engagement, employing Social Cognitive Theory (SCT) as the theoretical framework. In June and July 2023, 424 participants were chosen from public vocational institutions in Hubei Province, Central China, using the simple random sampling method. Results were analyzed utilizing structural equation modeling (SEM) in AMOS 24.0 and SPSS 26.0. The findings indicated a significant correlation between digital technology usage and student satisfaction. Moreover, the digital technology usage exhibited an indirect and positive correlation with student satisfaction of vocational students through learning experience and learning engagement, respectively. The findings highlight the importance of learning experience as a crucial element connecting digital technology usage to student satisfaction. This study urges administrators and educators to recognize the significance of learning experiences and learning engagement in the use of digital technology, fosters a supportive educational environment through digital resources, facilitates substantial changes in teaching and learning in higher vocational education, and executes strategies to connect academia with industry. This study’s distinctiveness lies in its enhancement of theoretical understanding of digital technology usage by investigating the mechanisms via which it affects student satisfaction. This clarifies the complex interconnections among digital technology usage, learning experience, learning engagement, and student satisfaction, emphasizing the mediating roles of learning experience and learning engagement in the Chinese context.